Crystal Structure of 3-Chloromethyl-(3-phenyl-oxiranyl)phenyl Methanone: New Monoclinic Polymorph - Nadeem Arshad, Muhammad; M. Asiri, Abdullah; A. Alamry, Khalid; S. Al-Juaid, Salih; Bahadar Khan, Sher; Hussain Bokhari, Tanveer; Shafiq, Muhammad (Asian Journal of Chemistry, 2014)
The compound, 3-chloromethyl-(3-phenyl-oxiranyl)phenyl methanone [m.f. C16H13O2Cl] was a self-condensation product of phenacyl chloride where the reaction carried out in ethanol medium using inorganic base. This was crystalized in monoclinic with space group P21/c (no. 14), a = 10.1312 (2) Å, b = 11.7728 Å, c = 11.8566 Å, V = 1344.07 Å3, Z = 4 and rcalc. = 1.348 mg/mm3. The dihedral angle between two aromatic rings is 73.46 (5). The epoxide ring is oriented at dihedral angles of 62.12 (9°) and 60.87 (7°) with respect to the phenyl and benzoyl rings. The non-classical intermolecular hydrogen bonding of C-H···O type has been observed in the crystal structure of molecule.